2005
DOI: 10.1097/00003446-200504000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Development of Audiovisual Comprehension Skills in Prelingually Deaf Children With Cochlear Implants

Abstract: The results suggest that lipreading skills and AV speech perception reflect a common source of variance associated with the development of phonological processing skills that is shared among a wide range of speech and language outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
92
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 61 publications
8
92
3
Order By: Relevance
“…This finding differs from those of Bergeson et al (16) who found a significant relationship between visual-only word recognition and performance on measures of language processing. The contrasting results probably are due to differences in the participant characteristics between our study and that of Bergeson et al (16). They longitudinally examined audiovisual word recognition in a group of children with profound deafness who received a CI before 9 years of age.…”
Section: The Relationship Between Spoken Word Recognition and Languagcontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding differs from those of Bergeson et al (16) who found a significant relationship between visual-only word recognition and performance on measures of language processing. The contrasting results probably are due to differences in the participant characteristics between our study and that of Bergeson et al (16). They longitudinally examined audiovisual word recognition in a group of children with profound deafness who received a CI before 9 years of age.…”
Section: The Relationship Between Spoken Word Recognition and Languagcontrasting
confidence: 99%
“…When administered a recorded, open-set test of sentence recognition, the participants were best at identifying key words in the AV presentation format, followed by the A-only and V-only presentation formats, respectively. This finding is consistent with previous studies concerning audiovisual spoken word recognition in adult CI users tested with isolated words (22) and in pediatric CI recipients tested with sentences presented via live voice (16). Mean scores for the AV and A-only presentation formats were generally quite high.…”
Section: Auditory-visual Speech Integrationsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous research has demonstrated that early identification of hearing loss and subsequent intervention methods and choices have a significant impact on infants' linguistic and cognitive development (Bergeson et al, 2003(Bergeson et al, , 2005Houston et al, 2003;Moeller, 2000;Pisoni et al, 2008;Yoshinaga-Itano et al, 1998). Research with normal-hearing infants suggests that both the quality (Kaplan et al, 2002;Kaplan et al, 1999;Liu et al, 2003) and quantity (Hart and Risley, 1995;Hurtado et al, 2008) of infant-directed (ID) speech is directly related to infants' language, cognitive, and socio-emotional development.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the implant users rely more than normal listeners on the visual cue, forcing them to become not only better speechreaders but also better multi-sensory integrators (Goh et al, 2001;Clark, 2003;Schorr et al, 2005;Rouger et al, 2007). Indeed, some cochlear-implant users can integrate AV cues to increase the functional SNR in noise (Lachs et al, 2001;Bergeson et al, 2005;Hay-McCutcheon et al, 2005;Moody-Antonio et al, 2005).…”
Section: Introductionmentioning
confidence: 99%